Challenges in the last mile of the global guinea worm eradication program - Lemma, Getahun Weldu; Müller, Olaf; Reñosa, Mark Donald; Lu, Guangyu (Tropical medicine & international health, 2020)
Objective The objective of this study was to identify the existing challenges in the last mile of the global Guinea Worm Eradication Program. Methods Systematic Review of articles published from 1 January 2000 until 31 December 2019. Papers listed in Cochrane Library, Google Scholar, ProQuest PubMed and Web of Science databases were searched and reviewed. Results Twenty-five articles met inclusion criteria of the study and were selected for analysis. Hence, relevant data were extracted, grouped and descriptively analysed. Results revealed 10 main challenges complicating the last mile of global guinea worm eradication: unusual mode of transmission; rising animal guinea worm infection; suboptimal surveillance; insecurity; inaccessibility; inadequate safe water points; migration; poor case containment measures, ecological changes; and new geographic foci of the disease. Conclusion This systematic review shows that most of the current challenges in guinea worm eradication have been present since the start of the campaign. However, the recent change in epidemiological patterns and nature of dracunculiasis in the last remaining endemic countries illustrates a new twist. Considering the complex nature of the current challenges, there seems to be a need for a more coordinated and multidisciplinary approach of dracunculiasis prevention and control measures. These new strategies would help to make history by eradicating dracunculiasis as the first ever parasitic disease.
Gesehen am 10.02.2024